Observability of ionospheric space‐time structure with ISR: A simulation study. Issue 2 (15th February 2017) - Swoboda, John; Semeter, Joshua; Zettergren, Matthew; Erickson, Philip J.
Abstract: The sources of error from electronically steerable array (ESA) incoherent scatter radar (ISR) systems are investigated both theoretically and with use of an open‐source ISR simulator, developed by the authors, called Simulator for ISR (SimISR). The main sources of error incorporated in the simulator include statistical uncertainty, which arises due to nature of the measurement mechanism and the inherent space‐time ambiguity from the sensor. SimISR can take a field of plasma parameters, parameterized by time and space, and create simulated ISR data at the scattered electric field (i.e., complex receiver voltage) level, subsequently processing these data to show possible reconstructions of the original parameter field. To demonstrate general utility, we show a number of simulation examples, with two cases using data from a self‐consistent multifluid transport model. Results highlight the significant influence of the forward model of the ISR process and the resulting statistical uncertainty on plasma parameter measurements and the core experiment design trade‐offs that must be made when planning observations. These conclusions further underscore the utility of this class of measurement simulator as a design tool for more optimal experiment design efforts using flexible ESA class ISR systems. Key Points: Developed a full simulation for ESA ISR called SimISR Discussed errors sources from ISR processing along with simulation method Showed various examples from SimISR including case using multifluid ionosphere model as input